2018
DOI: 10.1016/j.jphotobiol.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Photomodulation multiple sessions as a promising preventive therapy for medication-related osteonecrosis of the jaws after tooth extraction in rats

Abstract: The aim of this study was to evaluate the effects of photobiomodulation (PBM) with multiple sessions of low-level laser on the alveolar repair process of rats with major risk factors for medication-related osteonecrosis of the jaws (MRONJ). Senile rats received 0.45 mL of vehicle (VEH and VEH-PBM) or 0.45 mL of 100 μg/kg zoledronate (ZOL and ZOL-PBM) administrated intraperitoneally every two days during seven weeks. After three weeks of initiation of drug treatment the first lower left molar was extracted. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 53 publications
0
24
0
2
Order By: Relevance
“…The ligature was maintained for three weeks in order to induce experimental periodontitis (EP) (Fig. 6C) 67,68 .
Figure 6Experimental design. ( A ) Scheme illustrating experimental procedures performed during the study.
…”
Section: Methodsmentioning
confidence: 99%
“…The ligature was maintained for three weeks in order to induce experimental periodontitis (EP) (Fig. 6C) 67,68 .
Figure 6Experimental design. ( A ) Scheme illustrating experimental procedures performed during the study.
…”
Section: Methodsmentioning
confidence: 99%
“…LLL therapy, which is also called photobiomodulation, has properties that could favor the process of tissue repair. 15,31 LLL therapy is able to modulate the metabolism of human osteoblasts by increasing their proliferation and differentiation. 32 Moreover, LLL therapy is claimed to have beneficial analgesic and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Other reactions increase cell proliferation and cell differentiation when they occur, involving the transduction of signals to the cytoplasm level. 14 Previous animal studies by our research group 15 and other research groups [16][17][18] have shown that LLL therapy after extraction improves the alveolar repair process. Similarly, clinical studies have also indicated that LLL therapy has positive effects on the main signs and symptoms during the post-extraction wound healing process.…”
Section: Introductionmentioning
confidence: 92%
“…The negative controls consisted of specimens submitted to the procedures previously mentioned without the primary antibodies (Benetti et al 2018b, Dal-Fabbro et al 2019. With the aid of image analysis software (91000, Leica LAS 4.12; Leica Microsystems), the area corresponding to immunolabeling was delineated using the colour threshold tool to obtain the immunolabeling optical density, expressed as random unit percentage of optical density (mean AE SD) (Azuma et al 2018, Statkievicz et al 2018.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%